Role of Artificial Intelligence Adoption and Digital Transformation in Enhancing Sustainable Business Performance: The Mediating Effect of Green Product Innovation - Rana, Bikash; Acharya, Bikash (Devkota Journal of Interdisciplinary Studies, 2025)
In the context of Nepal’s increasing vulnerability to environmental challenges, this study explores how emerging technologies – namely Digital transformation and artificial intelligence (AI) can help businesses operate sustainably practices. It specifically examines the role of green product innovation as a bridge between technological advancement and sustainable outcomes. Drawing on data from 384 firms, the research applies structural equation modeling (PLS-SEM) to evaluate key relationships. The results indicate that both the adoption of AI and the process of digital transformation contribute positively to environmental and operational performance, with green innovation acting as a critical mediator. While AI supports smarter decision-making and resource efficiency, digital tools improve operational transparency and customer engagement. When integrated, these technologies enable firms to align business goals with broader sustainability agendas. The study offers timely insights for policymakers, business leaders, and researchers focused on driving sustainable innovation in developing economies.